Queueing analysis for preemptive transmission in underlay CRNs. (23rd October 2015) - Chen, Long; Huang, Liusheng; Xu, Hongli; Du, Yang
Summary: In cognitive radio applications, there are multiple different types of message queues. Existing queueing based works in underlay cognitive radio networks mainly focused on homogeneous packets. Therefore, we propose a new underlay scheme to deal with packets' heterogeneity by assuming high‐priority packets have preemptive transmission opportunities over low‐priority ones, and the former ones have impatient waiting time. We model the secondary user packets' behavior as a M/M/1+GI queueing system from the perspective of the whole system, which is represented by a two‐dimensional state transition graph. The reneging probability of high‐priority packets and the average waiting time in two‐class priority queues are analyzed. Then we extend the single‐channel model to multiple channels. Under this scenario, the closed form of low‐priority packets' expected system delay is derived. Simulation results demonstrate that the average waiting time of high‐priority packets decreases with the growing interference power threshold and the average waiting time of the low‐priority packet is proportional to the arrival rate of high‐priority packet and so on. This work may lay the foundation to design efficient Medium Access Control protocols and optimize long‐term system performance by carefully choosing system parameters. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We propose a new underlay scheme to deal with packets' heterogeneity by assuming that high‐priority packets have preemptive transmission opportunities over low‐priority ones, and the former ones have impatient waiting time. The reneging probability of high‐priority packets and the average waiting time in two‐class priority queues are analyzed. Then, we extend the single‐channel model to multiple channels.